2007
DOI: 10.1523/jneurosci.2827-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Transcranial Magnetic Stimulation Has Opposing Effects on Visual and Auditory Stimulus Detection: Implications for Multisensory Interactions

Abstract: Multisensory interactions occur early in time and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
119
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 62 publications
30
119
4
Order By: Relevance
“…The requisite anatomy for such interactions has been well documented (Falchier et al, 2002(Falchier et al, , 2010Rockland and Ojima, 2003;Cappe and Barone, 2005) and may even include a corticothalamocortical loop (Cappe et al, 2007a(Cappe et al, , 2009cHackett et al, 2007). When considered in conjunction with functional studies showing multisensory interactions in low-level cortices and/or at early latencies (Ghazanfar and Schroeder, 2006;Bizley et al, 2007;Cappe et al, 2007b;Martuzzi et al, 2007;Romei et al, 2007Romei et al, , 2009Bizley and King, 2008;Kayser et al, 2008;Wang et al, 2008;Raij et al, 2010), we consider it probable that the present phenomena are supported by direct interconnections that at a functional level are likely a combination of feedforward as well as feedback activity.…”
Section: Discussionmentioning
confidence: 57%
“…The requisite anatomy for such interactions has been well documented (Falchier et al, 2002(Falchier et al, , 2010Rockland and Ojima, 2003;Cappe and Barone, 2005) and may even include a corticothalamocortical loop (Cappe et al, 2007a(Cappe et al, , 2009cHackett et al, 2007). When considered in conjunction with functional studies showing multisensory interactions in low-level cortices and/or at early latencies (Ghazanfar and Schroeder, 2006;Bizley et al, 2007;Cappe et al, 2007b;Martuzzi et al, 2007;Romei et al, 2007Romei et al, , 2009Bizley and King, 2008;Kayser et al, 2008;Wang et al, 2008;Raij et al, 2010), we consider it probable that the present phenomena are supported by direct interconnections that at a functional level are likely a combination of feedforward as well as feedback activity.…”
Section: Discussionmentioning
confidence: 57%
“…As mentioned earlier (see also other chapters in this issue), many human studies conducted with EEG or fMRI have revealed multisensory interactions in low-level cortices such as V1 (see Ghazanfar and Schroeder, 2006 for a review and Martuzzi et al, 2007;Romei et al, 2007Romei et al, , 2008 for recent evidences) and/or at a latency that strongly suggests that such phenomena are supported by the heteromodal connections directly linking areas of different sensory modalities. For example, the visual information derived from the lip movements during speech processing can affect directly the responses recorded in the auditory cortex (Besle et al, 2004).…”
Section: Electrophysiological Evidence In the Primary Sensory Areasmentioning
confidence: 83%
“…The notion that multisensory integration is restricted to higherorder areas has recently been challenged by human and animal studies that have revealed that crossmodal interactions can occur in unisensory areas at very low levels of cortical processing (Buchel et al, 1998;Calvert et al, 1999Calvert et al, , 2001Macaluso et al, 2000;Schroeder et al, 2001;Amedi et al, 2002;Ghazanfar et al, 2005;Kriegstein et al, 2005;Miller and D'Esposito, 2005;Watkins et al, 2006;Martuzzi et al, 2007;Kayser et al, 2007Kayser et al, , 2008Romei et al, 2007Romei et al, , 2008Wang et al, 2008) and more importantly at very short latencies (Giard and Peronnet, 1999;Foxe et al, 2000;Molholm et al, 2002;Murray et al, 2005;Senkowski et al, 2007;Sperdin et al, 2009). Such a fast timing of multisensory interactions rule out an origin in the multisensory areas mediated through backward projections, and instead favor direct heteromodal connections.…”
Section: Heteromodal Connections: Connections Between Different Sensomentioning
confidence: 99%
“…Spierer et al 2013;Sutherland et al 2014). For example, visual cortex excitability, driven by a TMS pulse over occipital areas and measured by phosphene perception, can be enhanced by concomitant presentation of sounds as early as 60-75ms before the TMS stimulation onset (Romei et al 2007).…”
Section: Early Msi As a Hallmark Of A Bottom-up Multisensory Processmentioning
confidence: 99%